1996
DOI: 10.1117/12.251936
|View full text |Cite
|
Sign up to set email alerts
|

<title>Effects of the Nd:YAG laser on amalgam dental restorative material: a preliminary study</title>

Abstract: The Nd:YAG laser has been marketed as an instrument for use on both hard and soft dental tissues. Its potential for use on hard tissues is limited but it may be the instrument of choice for use in certain soft tissue procedures. The aim of this study was to examine the effects of the Nd:YAG laser on amalgam restorations which frequently occur on tooth surfaces adjacent to areas of soft tissue which may be subjected to the laser. The amalgam used was Tytin. The laser firing was controlled by a computer and a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Madani et al (Madani et al 2013) investigated the effect of Nd-YAG laser irradiation to alloy surface and found no significant difference on shear bond strength between resin cement and alloy. Er:YAG laser system, with or without water, can ablate restorative materials, and the presence of water does not decrease the efficiency of ablation, though it prevents temperature rise (Cernavin et al 1999). The ablation process and the formation of crater-like scratches probably achieves micro mechanic retention and it causes, increase the bonding values.…”
Section: Discussionmentioning
confidence: 99%
“…Madani et al (Madani et al 2013) investigated the effect of Nd-YAG laser irradiation to alloy surface and found no significant difference on shear bond strength between resin cement and alloy. Er:YAG laser system, with or without water, can ablate restorative materials, and the presence of water does not decrease the efficiency of ablation, though it prevents temperature rise (Cernavin et al 1999). The ablation process and the formation of crater-like scratches probably achieves micro mechanic retention and it causes, increase the bonding values.…”
Section: Discussionmentioning
confidence: 99%
“…Since GIC contains 20–50% percent water in its set form, and since Erbium lasers target the water molecules in their irradiation area GIC is likely more susceptible to surface defects from Er,Cr:YSGG lasers than from other types. Earlier studies have tried different types of laser in various modes and in different power options to expose this effect (Mazouri and Walsh, ; Cernavin and Hogan, ; Kilinc et al ., ; Hatipoglu and Barutcigil, ). Er,Cr:YSGG lasers showed a significant effect on GIC in terms of surface roughness and left deep traces in the SEM and AFM images.…”
Section: Discussionmentioning
confidence: 99%
“…In the examination of amalgam samples, the results of the surface roughness test, which were verified by SEM and AFM images, revealed that neither the Er,Cr:YSGG laser nor the diode laser left a noticeable trace on the surface. Studies that investigated the effects of different lasers on AM reported that lasers cause differently shaped defects in amalgam (Cernavin and Hogan, ; Kilinc et al ., ). Kilinc et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A computer simulation was carried out applying the laser beam normal to location P 1 (Figure 4(a)). An initial time step of 10 −6 s was selected and the simulation was carried out until the final time of 5 s, which corresponds to a typical laser treatment time [22]. The target relative error was 5%.…”
Section: Adaptive Solution Of Laser Heating Of the Toothmentioning
confidence: 99%